Interleukin‐13 induces paralysis of Haemonchus contortus larvae in vitro. (8th June 2020) - Shepherd, Elizabeth; Greiner, Scott P.; Russ, Brynnan; Bowdridge, Scott A.
Abstract: Aims: Interleukin‐13 (IL‐13) is a Th2‐associated cytokine that typically induces gut contractility and mucus secretion to eliminate helminth parasites from the digestive tract. Little evidence exists of IL‐13's direct effect on Haemonchus contortus larvae (L3) and thus was the objective of this study. Methods: To test effects of IL‐13 on H contortus, L3 were treated with ovine recombinant (r) IL‐13 (1 μg/mL); motility and morbidity were assessed. Monocytes isolated from H contortus ‐resistant St. Croix (STC) and susceptible Suffolk (SUF) sheep were treated with anti–IL‐13 blocking antibody to elucidate differences in host immune response. Results: rIL‐13 treatment reduced L3 speed (27 μm/s) and distance (7.5 μm) compared to untreated L3 (speed: 94 μm/s; distance: 27 μm) ( P  < .001). Comparison of larval speed to known paralytic levamisole (LEV) revealed no difference between treatments (rIL13: 23 μm/s; LEV 27 μm/s). Additionally, rIL‐13 had no effect on larval morbidity. Blocking IL‐13 reduced monocyte‐driven larval morbidity (0.13 μmol/L ATP) and increased larval motility (88 μm/s; 27 μm) compared to larvae treated with STC‐monocytes alone (0.07 μM ATP; 34 μm/s; 8 μm) ( P  < .05). Conclusions: These data indicate IL‐13 has a dual capability paralysing L3 and contributing to monocyte‐driven larval morbidity, and also indicate breed differences.